Gas tungsten arc-welding method

The TIG welding method with a nitrogen-enriched shield gas stabilizes the weld metal composition, addressing high-temperature cracking and enhancing strength in high-Mn steels for low-temperature applications, achieving improved mechanical properties.

JP2025012384AActive Publication Date: 2025-01-24JFE STEEL CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023115178
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-24
Estimated Expiration
2043-07-13

AI Technical Summary

Technical Problem

Existing welding methods for high-Mn-containing austenitic steels used in extremely low-temperature environments face challenges in achieving high strength and preventing high-temperature cracking, particularly when applying TIG welding, as they often require expensive materials and are prone to cracking due to impurity segregation during solidification.

Method used

A TIG welding method that uses a shield gas containing 0.5% to 10.0% nitrogen, along with other inert gases, to stabilize the weld metal composition, reducing impurity segregation and enhancing the strength of the weld joint, thereby suppressing high-temperature cracking.

Benefits of technology

The method improves the strength of weld metals and suppresses high-temperature cracking, achieving a yield stress of 400 MPa or more, tensile strength of 600 MPa or more, and Charpy shock absorption energy of 28J or more at -196°C, while maintaining excellent low-temperature impact toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012384000001_ABST
    Figure 2025012384000001_ABST
Patent Text Reader

Abstract

To provide a gas tungsten arc-welding method capable of more suppressing generation of high temperature crack, by further improving strength of a weld metal, without changing a host material or a weld material, as a weld joint for high Mn steel used under cryogenic environment.SOLUTION: In a gas tungsten arc-welding method in which a steel is formed into a weld metal using a shield gas and a filler material, a metal structure of the steel has an austenite phase, a manganese content of the steel is 18.0% to 30.0% by mass, the shield gas contains 0.5% to 10.0% nitrogen gas by volume, and the remainder consists of inert gas and unavoidable impurities.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a gas tungsten arc welding method, and more particularly to a method for welding austenitic steel with a high Mn content that is used in an extremely low temperature environment. [Background technology]

[0002] Gas tungsten arc welding is a method of welding by melting a filler material (welding rod) in an arc while blocking the atmosphere by spraying inert gases, generally argon gas or helium gas, using tungsten, a non-consumable material, as an electrode rod. This welding method is also called Tungsten Inert Gas welding (hereinafter abbreviated as "TIG welding"). This TIG welding can be applied to even more complex shapes, such as various alloy steels and non-ferrous metals, and can produce excellent weld quality.

[0003] In recent years, environmental regulations have become stricter. Among them, liquefied natural gas (hereinafter, also referred to as LNG) is said to be a clean fuel that does not generate air pollutants such as sulfur oxides because it does not contain sulfur, and the demand for LNG is increasing. In order to transport or store LNG, containers (tanks) for transporting or storing LNG are required to maintain excellent cryogenic impact toughness at temperatures below -162°C, which is the liquefaction temperature of LNG.

[0004] Because of the need to maintain this excellent cryogenic impact toughness, aluminum alloys, 9% Ni steel, austenitic stainless steel, and the like have conventionally been used as materials for containers (tanks) and the like.

[0005] However, aluminum alloys have low tensile strength, which requires the plate thickness of the structure to be large, and they also have problems with poor weldability. In addition, 9% Ni steel requires the use of expensive Ni-based materials as welding materials, which is economically disadvantageous.

[0006] Therefore, TIG welding technology using austenitic stainless steel is being considered.

[0007] For example, Patent Document 1 discloses an austenitic steel welded joint in which an austenitic steel base material having a specific composition is welded by a gas tungsten arc welding method using an austenitic steel welding material having a specific composition. The main composition of the weld metal is C≦0.1%, Si≦0.8%, Mn: 1.5-5.5%, Ni: 8-15%, Cr: 18-24%, Al<0.05%, N: 0.15-0.35%, and the amount of ferrite in the weld metal is 20% or less in area ratio. It also discloses that in gas tungsten arc welding, in addition to Ar gas, N2 gas is mixed into the shielding gas at 50 volume % or less.

[0008] However, austenitic stainless steel has problems in that it is expensive and has low base metal strength. For this reason, the application of high-Mn-content austenitic steel (hereinafter also referred to as "high Mn steel") containing about 10 to 35 mass% Mn has been considered recently as a material for containers (tanks) for transporting or storing LNG. The metal structure of high Mn steel has an austenite phase even at extremely low temperatures, does not suffer from brittle fracture, and has higher strength than austenitic stainless steel. Therefore, there has been a demand for the development of welding materials that can stably weld such high Mn steel.

[0009] In response to such demands, for example, Patent Document 2 discloses a "high Mn steel for cryogenic use." This steel contains, by mass%, C: 0.001-0.80%, Mn: 15.0-35.0%, S: 0.001-0.01%, Cr: 0.01-10.0%, Ti: 0.001-0.05%, N: 0.0001-0.10%, and O: 0.001-0.010%. In addition, P is limited to 0.02% or less, and contains one or both of Si: 0.001-5.00% and Al: 0.001-2.0%, and contains one or more of Mg: 0.01% or less, Ca: 0.01% or less, and REM: 0.01% or less in total of 0.0002% or more. The steel satisfies 30C+0.5Mn+Ni+0.8Cr+1.2Si+0.8Mo≧25··· (formula 1) and O / S≧1··· (formula 2), with the balance being Fe and unavoidable impurities. The steel is a high Mn steel for cryogenic use, with an austenite volume fraction of 95% or more, a crystal grain size of the austenite of 20 to 200 μm, and a carbide coverage rate at the grain boundaries of the austenite of 50% or less. The steel of Patent Document 2 controls the austenite grain size to an appropriate size, appropriately adjusts the amounts and balance of alloy elements added, as well as the amount of S and the amount of O, and adds Mg, Ca, and REM, so that carbides formed at the grain boundaries do not become the starting point of fracture or the path of crack propagation. As a result, the austenite grain size can be appropriately adjusted, and coarsening of the grain size of the welded heat affected zone can be suppressed.

[0010] Patent Document 3 discloses a "thick steel plate for low temperature use". This thick steel plate contains, in mass%, C: 0.30 to 0.65%, Si: 0.05 to 0.30%, Mn: more than 20.00% and less than 30.00%, Ni: 0.10% or more and less than 3.00%, Cr: 3.00% or more and less than 8.00%, and Al: 0.005 to 0.100%. In addition, it contains N: 0.0050% or more and less than 0.0500%, P: 0.0040% or less, S: 0.020% or less, O: 0.0050% or less, and the balance is Fe and impurities. Furthermore, it is said that the Mn segregation ratio XMn (XMn = Mn1 / Mn0) calculated from the Mn concentration Mn1 in the Mn-rich part and the Mn concentration Mn0 in the Mn-lean part is 1.6 or less. And, the yield stress at room temperature (25℃) is 400MPa or more, the tensile stress is 800MPa or more, and the Charpy impact absorption energy of the welded heat affected zone ( v E -196 ) is 70 J or more. According to the technology described in Patent Document 3, it is described that the hot-rolled steel can be provided as a material for containers (tanks) for transporting or storing LNG.

[0011] In general, design stresses based on the strength characteristics of the base metal or weld metal are used in the design of welded structures. In recent years, many welded structures, including LNG tanks, have been designed to be larger, which requires higher strength joints.

[0012] However, according to the study by the present inventors, there was a problem that hot cracks may occur if the weld metal has high strength even if the TIG welding method described in Patent Document 1 is applied to the welding of high Mn steel materials described in Patent Documents 2 and 3. Furthermore, when high strength weld metal is required, it is necessary to change the composition of the base metal or welding material, and it has been difficult to increase the strength of the weld metal by the welding method alone.

[0013] Therefore, as disclosed in Patent Document 4, the present inventors have developed a TIG welded joint for high Mn steel that can suppress the occurrence of hot cracking during welding and has high strength and excellent cryogenic impact toughness. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] International Publication No. WO2013 / 005570 [Patent Document 2] JP 2016-196703 A [Patent Document 3] JP 2017-071817 A [Patent Document 4] Patent No. 7188647 Summary of the Invention [Problem to be solved by the invention]

[0015] However, in response to recent demands for even higher strength and improved hot cracking resistance, the present inventors have investigated further improvements in the gas tungsten arc welding method for high Mn steel.

[0016] An object of the present invention is to provide a gas tungsten arc welding method that can further improve the strength of the weld metal and further suppress the occurrence of hot cracking for welded joints of high-Mn steel used in cryogenic environments without changing the base metal or welding material. [Means for solving the problem]

[0017] In order to achieve the above-mentioned object, the present inventors first conducted extensive research into factors that affect hot cracking during TIG welding of high Mn steel. As a result, they found that one of the factors that causes hot cracking is the segregation of impurity elements in the final solidified portion of the weld metal. They also found that the segregation of impurity elements becomes significant when the temperature range from the start of solidification to the end of solidification is large during the solidification of the weld metal. They also found that when the weld metal becomes hotter than the solidus due to the thermal influence of welding after the next welding pass and liquefies, the segregation becomes significant when the temperature range from the start of resolidification to the end of resolidification (hereinafter also referred to as "solid-liquid coexistence temperature range") is large.

[0018] Next, the weld metal composition necessary for a welded joint produced by TIG welding in accordance with the provisions of JIS Z 3121 to have the desired high strength was studied. As a result, it was found that when N is contained in the weld metal composition of high Mn steel, the strength of the weld metal and the welded joint is improved by solid solution strengthening. Furthermore, it was found that increasing the content of N has the effect of narrowing the solid-liquid coexistence temperature range, and is an additive element that suppresses the occurrence of hot cracking in high Mn steel. Therefore, since N is an element that becomes N2 molecules at room temperature and normal pressure and is stable as a gas, a shielding gas containing 0.5 volume % to 10.0 volume % nitrogen gas (hereinafter also simply referred to as "N2 gas") and the remainder consisting of inert gas and unavoidable impurities was used during TIG welding. It was found that N can be stably dissolved in the weld metal.

[0019] The present invention was completed based on these findings and through further investigation.

[0020] The gist of the present invention is as follows. [1] In a gas tungsten arc welding method in which steel is welded using a shielding gas and a filler metal, The metal structure of the steel material has an austenite phase, The Mn content of the steel material is 18.0% to 30.0% by mass, The shielding gas contains 0.5% to 10.0% by volume of nitrogen gas, with the remainder being an inert gas and unavoidable impurities. 4. A gas tungsten arc welding method comprising the steps of: [2] In the above [1], the steel material further comprises, in mass%, C: 0.10%~0.70%, Si: 0.05% to 1.00%, P:0.030% or less, S: 0.007% or less, Al: 0.010%~0.070%, Cr: 2.5%~7.0%, N: 0.0050%~0.0500%, O (oxygen): 0.0050% or less The balance is Fe and unavoidable impurities. 4. A gas tungsten arc welding method comprising the steps of: [3] In the above [2], the steel material further comprises, in mass%, Mo: 0.01% to 2.00%, V: 0.01%~2.00%, W: 0.01% to 2.00%, Ni: 0.01%~4.00%, REM: 0.0010%~0.0200% and B: 0.0005% to 0.0020% Contains one or more of the following: 4. A gas tungsten arc welding method comprising the steps of: [4] In any one of the above [1] to [3], the filler metal is, in mass%, C: 0.20%~0.80%, Si: 0.15% to 1.00%, Mn: 17.0% to 30.0%, P: 0.030% or less, S: 0.030% or less, Ni: 0.01% to 10.00%, Cr: 0.4%~4.0%, Mo: 0.01% to 3.50%, B: 0.0010% or less, N: 0.1200% or less The balance is Fe and unavoidable impurities. 4. A gas tungsten arc welding method comprising the steps of: [5] In the above [4], the filler metal further comprises, in mass%, V: 0.01%~0.04%, Ti: 0.010%~0.040%, Nb: 0.010%~0.040%, Cu: 0.01% to 1.00%, Al: 0.010% to 0.100% and W: 0.01% to 1.00% Contains one or more of the following: 4. A gas tungsten arc welding method comprising the steps of: [6] In the gas tungsten arc welding method according to any one of [1] to [5], Welding current is 180A~250A, Welding voltage is 10V~20V, Welding speed: 5cm / min~30cm / min, Welding heat input is 7.0kJ / cm~40.0kJ / cm 4. A gas tungsten arc welding method comprising the steps of: [7] In any one of the above [1] to [6], the yield stress (0.2% proof stress) of the weld metal is 400 MPa or more, the tensile strength is 600 MPa or more, and the Charpy impact absorption energy ( v E -196 ) is 28J or more 4. A gas tungsten arc welding method comprising the steps of: Effect of the Invention

[0021] By using the gas tungsten arc welding method of the present invention, it is possible to easily produce a welded joint for high-Mn steel used in an extremely low-temperature environment, which has further improved strength of the weld metal and can further suppress the occurrence of hot cracking, thereby providing significant industrial benefits. [Brief description of the drawings]

[0022] [Figure 1] FIG. 2 is a schematic diagram showing an example of a groove shape in the TIG welding method of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a test piece sampling position for a Charpy impact test. [Diagram 3] FIG. 4 is a graph showing the change in 0.2% proof stress versus the N content in the weld metal. [Figure 4] FIG. 1 is a graph showing the change in tensile strength relative to the N content in a weld metal. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] As described above, the present invention is a gas tungsten arc welding (TIG welding) method that can further improve the strength of the weld metal and further suppress the occurrence of hot cracking as a weld joint for high Mn steel used in an extremely low temperature environment without changing the base metal or welding material. The weld joint produced by the welding method of the present invention is a weld joint produced by TIG welding in accordance with the provisions of JIS Z 3001-7 (excluding the type of shielding gas). Furthermore, compared with a general TIG welded joint in which the shielding gas is 99.5% or more of an inert gas and the balance is unavoidable impurities, the yield stress (0.2% proof stress) and tensile strength at room temperature (25°C) in a tensile test of the weld metal produced in accordance with the provisions of JIS Z 3111 are improved by an average of 10 MPa or more. Furthermore, the absorbed energy (hereinafter referred to as "absorbed energy") of a Charpy impact test at a test temperature of -196°C of the weld metal of a weld joint produced in accordance with the provisions of JIS Z 3128 is improved by an average of 10 MPa or more. v E -196 It has excellent cryogenic impact toughness with a cryogenic impact strength of 28J or more, and is free from high temperature cracking.

[0024] [Gas tungsten arc welding (TIG welding)] As mentioned above, TIG welding is a method that uses tungsten as an electrode rod, blows inert gas such as argon gas or helium gas as a shielding gas to block air, and melts a filler metal in the arc as needed to weld. This TIG welding can be used for welding various alloy steels and non-ferrous metals, and can also weld complex shapes, and can provide excellent welding quality, so it is used for welding all kinds of metals.

[0025] [Shielding gas] In the present invention, a shielding gas for arc welding is used as the shielding gas for TIG welding, which contains, by volume, 0.5% to 10.0% nitrogen (N2) gas, with the remainder being inert gas and unavoidable impurities. Note that, hereinafter, "%" in the gas component content means "volume %".

[0026] Here, in the present invention, the "inert gas" used as a shielding gas means argon (Ar) gas, helium (He) gas, or a mixed gas thereof. The content of this inert gas is preferably 90.0% to 99.5%, more preferably 93.0% to 99.5%, even more preferably 93.0% to 98.0%, and most preferably 95.0% to 98.0%.

[0027] In addition, the unavoidable impurities are gases other than nitrogen gas and the inert gases, and examples thereof include oxygen (O2) gas, hydrogen (H2) gas, and carbon dioxide (CO2) gas.

[0028] N is an element that, when dissolved in the weld metal of high Mn steel, improves the strength of the weld metal and welded joint by solid solution strengthening. Furthermore, when the content of N increases in the weld metal, it tends to narrow the solid-liquid coexistence temperature range, improving hot cracking susceptibility. In order to obtain such an effect, it is necessary to contain 0.5% or more of nitrogen (N2) in the shielding gas. Therefore, the nitrogen content in the shielding gas is set to 0.5% or more. It is preferably 0.8% or more, and more preferably 1.0% or more. On the other hand, if the nitrogen content in the shielding gas is 10.0% or more, the arc becomes unstable and welding defects such as blowholes and pits occur. Therefore, the nitrogen content in the shielding gas is set to 10.0% or less. It is preferably 8.0% or less, more preferably 6.0% or less, even more preferably 5.0% or less, and most preferably 4.5% or less.

[0029] The flow rate of the shielding gas is preferably 10 L / min to 30 L / min, and more preferably 15 L / min to 25 L / min.

[0030] [Welding method and conditions] Next, specific examples of welding conditions and the like relating to the TIG welding method will be described, one embodiment of which is shown in Fig. 1. The plate thickness t of the steel material that becomes the base material 1 is 5 mm to 102 mm.

[0031] When preparing the test pieces described later, the base materials 1 are butted together to form a V-groove with a groove angle θ of 35° to 60° in accordance with JIS Z 3111. A pure tungsten rod (2.5 mmφ to 4.0 mmφ) and a filler metal (diameter 1.5 mmφ to 2.5 mmφ) are used as electrodes for TIG welding, and preheating is not required.

[0032] Other welding conditions are current: 180A-250A (DCEN), voltage: 10V-20V, welding speed: 5cm / min-30cm / min, and welding heat input: 7.0kJ / cm-40.0kJ / cm. Here, if the welding heat input is less than 7.0kJ / cm, the deposition amount is insufficient, welding defects are likely to occur, and the efficiency is low, so it is not suitable for practical construction. On the other hand, if it exceeds 40.0kJ / cm, the electrodes are worn out and the frequency of replacement increases, which reduces the efficiency, and the stability of the arc decreases, which makes it easy for welding defects to occur. More preferably, it is 8.0kJ / cm-30.0kJ / cm, and even more preferably, it is 8.0kJ / cm-25.0kJ / cm. In addition, the interpass temperature is 100℃-150℃.

[0033] Examples of welding positions include downward, horizontal, upward, and vertical upward welding. The groove shape may be a V groove as shown in Fig. 1, a L groove, a K groove, an X groove, etc. As described above, the groove angle θ is preferably 35° to 60°, and more preferably 40° to 55°.

[0034] Under the above-mentioned welding conditions, a weld metal 2 is formed in the V-groove by single-layer or multi-layer welding, and the weld metal 2 has a form in which layers 2a of the weld metal are stacked in multiple layers. Note that if the welding method (welding conditions) of the present invention are not followed, welding defects such as solidification cracks 4 will occur in part of the weld metal layers 2a, but in the welding method of the present invention, such welding defects such as solidification cracks 4 will not occur.

[0035] [High Mn steel (high Mn-containing austenitic steel)] Next, the steel material to be the base material will be described. Any steel material may be used as long as it is a high Mn-containing austenitic steel. In the present invention, the high Mn content of the high Mn-containing austenitic steel means that the Mn content in the steel composition is 18.0% to 30.0% by mass. The austenitic steel of the high Mn-containing austenitic steel is a steel material whose base phase (metal structure) is an austenitic phase.

[0036] That is, when the crystal structure of a steel material is a body-centered cubic structure (bcc), the steel material is not suitable for use in a low-temperature environment because it may undergo brittle fracture in the low-temperature environment. When considering use in a low-temperature environment, the base phase of the metal structure of the steel material must be an austenite structure with a face-centered cubic (fcc) crystal structure. Note that "the base phase is an austenite phase" means that the austenite phase accounts for 90% or more of the area. The remainder other than the austenite phase is a ferrite phase or a martensite phase, or precipitates such as carbides. More preferably, the austenite phase accounts for 95% or more, and even more preferably, 100%.

[0037] [Basic composition of steel] Here, the chemical composition of the preferred steel material will be described below. Note that hereinafter, "%" in "chemical composition" means "mass %".

[0038] The steel material used in the present invention is a high Mn steel material containing 18.0% to 30.0% of Mn as described above. In addition, the contents of C: 0.10% to 0.70%, Si: 0.05% to 1.00%, P: 0.030% or less, S: 0.007% or less, Al: 0.010% to 0.070%, Cr: 2.5% to 7.0%, N: 0.0050% to 0.0500%, and O (oxygen): 0.0050% or less. The balance is preferably a high Mn steel having a chemical composition consisting of Fe, an arbitrary selected composition, and unavoidable impurities. The reasons for limiting the chemical composition are as follows.

[0039] [Mn: 18.0%~30.0%] Mn is a relatively inexpensive element that has the effect of stabilizing the austenite phase, and is an important element for achieving both high strength and excellent cryogenic impact toughness. In order to obtain such an effect, it is necessary to include 18.0% or more. Therefore, the Mn content is set to 18.0% or more. It is preferably 20.0% or more, more preferably 22.0% or more, and even more preferably 24.0% or more. On the other hand, even if it is included in more than 30.0%, the effect of improving the cryogenic impact toughness is saturated, and an effect commensurate with the content cannot be expected, which is economically disadvantageous. In addition, if it is included in a large amount exceeding 30.0%, it will cause a decrease in cuttability, promote Mn segregation, and promote the occurrence of stress corrosion cracking. Therefore, the Mn content is set to 30.0% or less. It is preferably 29.0% or less, more preferably 28.5% or less, and even more preferably 28.0% or less.

[0040] [C:0.10%~0.70%] C is an inexpensive and important element that stabilizes the austenite phase and improves the cryogenic impact toughness. In order to obtain such an effect, the C content is preferably 0.10% or more. More preferably, it is 0.20% or more, even more preferably, it is 0.25% or more, and most preferably, it is 0.35% or more. On the other hand, if the C content exceeds 0.70%, Cr carbides are excessively generated, and the cryogenic impact toughness may decrease. For this reason, the C content is preferably 0.70% or less. More preferably, it is 0.65% or less, even more preferably, it is 0.63% or less, and most preferably, it is 0.60% or less.

[0041] [Si: 0.05%~1.00%] Si acts as a deoxidizer and is an element that dissolves in steel and contributes to increasing the strength of steel material by solid solution strengthening. In order to obtain such an effect, the Si content is preferably 0.05% or more. More preferably, it is 0.07% or more, even more preferably, it is 0.10% or more, and most preferably, it is 0.20% or more. On the other hand, if it is contained in excess of 1.00%, the weldability may decrease. For this reason, the Si content is preferably 1.00% or less. More preferably, it is 0.80% or less, even more preferably, it is 0.70% or less, and most preferably, it is 0.60% or less.

[0042] [P:0.030% or less] P is an element that segregates to grain boundaries as an impurity and becomes the initiation point of stress corrosion cracking. In the present invention, it is desirable to reduce the P content as much as possible, but 0.030% or less is acceptable. Therefore, the P content is preferably 0.030% or less. More preferably, it is 0.028% or less, even more preferably, it is 0.024% or less, and most preferably, it is 0.015% or less. On the other hand, in order to extremely reduce the P content to less than 0.002%, a long refining time is required, and the refining cost rises. Therefore, from an economical point of view, the P content is preferably 0.002% or more.

[0043] [S:0.007% or less] S exists as sulfide-based inclusions in steel, and reduces the ductility and cryogenic impact toughness of steel and weld metal. For this reason, it is desirable to reduce S as much as possible, but 0.007% or less is acceptable. Therefore, the S content is preferably 0.007% or less. More preferably, it is 0.005% or less, and further preferably, it is 0.004% or less. On the other hand, in order to extremely reduce S to less than 0.0005%, a long refining time is required, and the refining cost rises. For this reason, from the viewpoint of economy, the S content is preferably 0.0005% or more.

[0044] [Al: 0.010%~0.070%] Al acts as a deoxidizer and is the most commonly used element in the molten steel deoxidation process for steel materials. In order to obtain such an effect, the Al content is preferably 0.010% or more. More preferably, it is 0.020% or more, and even more preferably, it is 0.030% or more. On the other hand, if the Al content exceeds 0.070%, Al may be mixed into the weld metal during welding, reducing the toughness of the weld metal. For this reason, the Al content is preferably 0.070% or less. More preferably, it is 0.060% or less, and even more preferably, it is 0.050% or less.

[0045] [Cr: 2.5%~7.0%] Cr is an element that stabilizes the austenite phase and effectively contributes to improving the cryogenic impact toughness and the strength of the steel material. It is also an effective element for forming a fine crystal region. In order to obtain such an effect, the Cr content is preferably 2.5% or more. More preferably, it is 3.0% or more, even more preferably, it is 3.3% or more, and most preferably, it is 4.0% or more. On the other hand, if the Cr content exceeds 7.0%, Cr carbides are generated, and the cryogenic impact toughness and stress corrosion cracking resistance may decrease. For this reason, the Cr content is preferably 7.0% or less. More preferably, it is 6.8% or less, even more preferably, it is 6.5% or less, and most preferably, it is 6.0% or less.

[0046] [N:0.0050%~0.0500%] N is an element that has the effect of stabilizing the austenite phase, and effectively contributes to improving the cryogenic impact toughness. In order to obtain such an effect, the N content is preferably 0.0050% or more. More preferably, it is 0.0060% or more, even more preferably, it is 0.0070% or more, and most preferably, it is 0.0080% or more. On the other hand, if it is contained in excess of 0.0500%, the nitrides or carbonitrides may become coarse during the steel manufacturing process, and the cryogenic impact toughness may decrease. For this reason, the N content is preferably 0.0500% or less. More preferably, it is 0.0450% or less, even more preferably, it is 0.0400% or less, and most preferably, it is 0.0350% or less.

[0047] [O (oxygen): 0.0050% or less] O (oxygen) exists as oxide-based inclusions in steel and reduces the cryogenic impact toughness of steel. For this reason, it is preferable to reduce O (oxygen) as much as possible, but 0.0050% or less is acceptable. For this reason, the O (oxygen) content is preferably 0.0050% or less. More preferably, it is 0.0045% or less, and further preferably, it is 0.0040% or less. On the other hand, in order to extremely reduce O (oxygen) to less than 0.0005%, a long refining time is required, and the refining cost rises. For this reason, from the viewpoint of economy, O (oxygen) is preferably 0.0005% or more. More preferably, it is 0.0006% or more.

[0048] [Optional composition of steel] The above-mentioned chemical composition is the preferred basic composition of high Mn steel, but in addition to this basic composition, the following optional compositions may be added as necessary: ​​Mo: 0.01%-2.00%, V: 0.01%-2.00%, W: 0.01%-2.00%, Ni: 0.01%-4.00%, REM: 0.0010%-0.0200%, and B: 0.0005%-0.0020%. The reasons for limiting each composition are as follows.

[0049] [Mo, V and W: 0.01% to 2.00%] Mo, V and W are elements that contribute to the stabilization of the austenite phase, and also contribute to improving the strength and cryogenic impact toughness of the steel material, and one or more of them can be selected and contained as necessary. In order to obtain such effects, it is preferable that the content of Mo, V and W is 0.01% or more. On the other hand, if the content of Mo, V and W exceeds 2.00%, the amount of coarse carbonitride increases, which becomes the starting point of fracture, and the cryogenic impact toughness decreases. Therefore, when Mo, V and W are contained, it is preferable that the content is 2.00% or less. More preferably, the content of Mo, V and W is 1.70% or less, and even more preferably, it is 1.50% or less.

[0050] [Ni:0.01%~4.00%] Ni is an element that contributes to stabilizing the austenite phase and strengthening the austenite grain boundaries, and also contributes to improving the cryogenic impact toughness of steel materials. In order to obtain such effects, the Ni content is preferably 0.01% or more. More preferably, it is 0.10% or more, and even more preferably, it is 0.20% or more. On the other hand, Ni is an expensive element, and a content exceeding 4.00% is economically disadvantageous. Therefore, the Ni content is preferably 4.00% or less. More preferably, it is 3.75% or less, and even more preferably, it is 3.50% or less.

[0051] [REM:0.0010%~0.0200%] REM is a rare earth element such as Sc, Y, La, or Ce, and has the effect of improving the toughness of steel material, as well as ductility and resistance to sulfide stress corrosion cracking, through controlling the morphology of inclusions. In order to obtain such an effect, the REM content is preferably 0.0010% or more, and more preferably 0.0015% or more. On the other hand, if it is contained in excess of 0.0200%, the amount of nonmetallic inclusions increases, and the toughness, ductility, and resistance to sulfide stress cracking may decrease. For this reason, the REM content is preferably 0.0200% or less, and more preferably 0.0180% or less.

[0052] [B:0.0005%~0.0020%] B is an element that segregates at grain boundaries and contributes to improving the toughness of steel. To obtain such an effect, the B content is preferably 0.0005% or more, and more preferably 0.0008% or more. On the other hand, if the B content exceeds 0.0020%, the amount of coarse nitrides and carbides increases, and the toughness may decrease. For this reason, the B content is preferably 0.0020% or less, and more preferably 0.0018% or less.

[0053] [Remainder of steel composition] The remaining composition other than the above-mentioned chemical composition is composed of Fe and inevitable impurities. Incidentally, examples of inevitable impurities include Ca, Mg, Ti, Nb, and Cu, and a total of 0.05% or less is acceptable. In addition, as long as the above-mentioned basic composition and optional composition are satisfied, elements other than these may be contained, and such embodiments are also included in the technical scope of the present invention.

[0054] [Manufacturing method of high Mn steel] Furthermore, a preferred method for producing the high Mn steel used in the present invention will be described. Note that a manufacturing method other than the method described below may be used as long as it can produce an equivalent high Mn steel, and the manufacturing method is not limited to the following method.

[0055] Molten steel having the above-mentioned steel composition is produced by a conventional melting method such as a converter or an electric furnace, and then produced into a steel material such as a slab having a predetermined size by a conventional casting method such as a continuous casting method or an ingot casting-blooming rolling method. In addition, secondary refining using a vacuum degassing furnace or the like may be performed during the production.

[0056] The obtained steel material is further heated, hot rolled and then cooled to obtain a steel material of a predetermined size. Note that, by heating at a heating temperature in the range of 1100°C to 1300°C, completing the hot rolling at a finish rolling end temperature of 790°C to 980°C, and immediately cooling, etc., a steel material with excellent cryogenic impact toughness can be obtained. In addition, in order to adjust the steel material properties, a heat treatment such as annealing treatment may be further performed.

[0057] Next, preferred mechanical properties of the high Mn steel used in the present invention will be described. The high strength steel for cryogenic use having the above-mentioned steel composition has a plate thickness of, for example, 5 mm to 102 mm, a yield stress (0.2% proof stress) Y S is 400MPa or more, and the Charpy impact absorption energy ( v E -196 ) is preferably 28 J or more. S More preferably, the tensile strength T S is 800MPa or more.

[0058] [Basic composition of filler metal] The present invention is a welding method for forming a welded joint by forming a weld metal part consisting of one or multiple layers of weld metal by TIG welding the above-mentioned high Mn steels together. The preferred chemical composition of the filler metal used in this case is shown below. In the following, "%" in the "chemical composition" of the filler metal means "mass %".

[0059] The basic composition of the filler metal used in the present invention is preferably as follows: C: 0.20% to 0.80%, Si: 0.15% to 1.00%, Mn: 17.0% to 30.0%, P: 0.030% or less, S: 0.030% or less, Ni: 0.01% to 10.00%, Cr: 0.4% to 4.0%, and Mo: 0.01% to 3.50%. Furthermore, the filler metal contains B: 0.0010% or less and N: 0.1200% or less, with the balance being Fe and unavoidable impurities. The reasons for limiting each of the compositions are as follows.

[0060] [C:0.20%~0.80%] C is an element that has the effect of increasing the strength of the weld metal by solid solution strengthening, and C is also an inexpensive and important element that has the effect of stabilizing the austenite phase and improving the cryogenic impact toughness of the weld metal. In order to obtain such effects, the C content is preferably 0.20% or more. More preferably, it is 0.25% or more, and even more preferably, it is 0.28% or more. On the other hand, if it is contained in excess of 0.80%, carbides are excessively generated in the weld metal, the cryogenic impact toughness decreases, and further, hot cracking during welding may easily occur. Therefore, the C content is preferably 0.80% or less. More preferably, it is 0.75% or less, even more preferably, it is 0.70% or less, and most preferably, it is 0.63% or less.

[0061] [Si:0.15%~1.00%] Si acts as a deoxidizer, increases the yield of Mn, increases the viscosity of the molten metal, and has the effect of stably maintaining the bead shape. In order to obtain such an effect, the Si content is preferably 0.15% or more. More preferably, it is 0.18% or more, even more preferably, it is 0.20% or more, and most preferably, it is 0.25% or more. On the other hand, if it is contained in excess of 1.00%, it may reduce the cryogenic impact toughness of the weld metal, and Si may segregate during solidification and generate a liquid phase at the solidification cell interface, thereby deteriorating the hot cracking resistance. Therefore, the Si content is preferably 1.00% or less. More preferably, it is 0.80% or less, even more preferably, it is 0.75% or less, and most preferably, it is 0.70% or less.

[0062] [Mn: 17.0%~30.0%] Mn is an inexpensive element that has the effect of stabilizing the austenite phase, but if the Mn content is less than 17.0%, a ferrite phase is generated in the weld metal, and the cryogenic impact toughness may be significantly reduced. For this reason, the Mn content is preferably 17.0% or more. More preferably, it is 18.0% or more, and even more preferably, it is 18.5% or more. On the other hand, if the Mn content exceeds 30.0%, the stacking fault energy increases and the resistance during deformation decreases, so that the strength may decrease. For this reason, the Mn content is preferably 30.0% or less. More preferably, it is 27.0% or less, and even more preferably, it is 26.0% or less.

[0063] [P:0.030% or less] P is an element that segregates at grain boundaries and induces hot cracking. In the present invention, it is preferable to reduce the P content as much as possible, but 0.030% or less is acceptable. Therefore, the P content is preferably 0.030% or less. More preferably, it is 0.020% or less, even more preferably, it is 0.018% or less, and most preferably, it is 0.014% or less. On the other hand, in order to extremely reduce the P content to less than 0.002%, a long refining time is required, and the refining cost rises. Therefore, from an economical point of view, the P content is preferably 0.002% or more.

[0064] [S:0.030% or less] S exists as sulfide-based inclusions MnS in the weld metal. MnS can be the starting point of fracture, and can reduce the cryogenic impact toughness. Therefore, the S content is preferably 0.030% or less, more preferably 0.025% or less, even more preferably 0.020% or less, and most preferably 0.017% or less. On the other hand, excessive reduction leads to an increase in refining costs. Therefore, the S content is preferably 0.001% or more.

[0065] [Ni:0.01%~10.00%] Ni is an element that strengthens austenite grain boundaries, and segregates at the grain boundaries to improve cryogenic impact toughness. Ni also has the effect of stabilizing the austenite phase, so if the Ni content is further increased, the austenite phase is stabilized and the cryogenic impact toughness of the weld metal is improved. In order to obtain such an effect, the Ni content is preferably 0.01% or more, and more preferably 1.00% or more. On the other hand, Ni is an expensive element, and a content exceeding 10.00% is economically disadvantageous. Therefore, the Ni content is preferably 10.00% or less, and more preferably 8.00% or less, further preferably 7.00% or less, and most preferably 6.00% or less.

[0066] [Cr:0.4%~4.0%] Cr is an element that stabilizes the austenite phase at cryogenic temperatures and effectively contributes to improving cryogenic impact toughness and weld metal strength. Cr also narrows the temperature range of the solid-liquid coexistence region of the molten metal and effectively acts to suppress the occurrence of hot cracks. In order to obtain such effects, the Cr content is preferably 0.4% or more. More preferably, it is 0.8% or more, even more preferably, it is 1.0% or more, and most preferably, it is 1.2% or more. On the other hand, if it is contained in excess of 4.0%, Cr carbides may be formed, which may lead to a decrease in cryogenic impact toughness. Therefore, the Cr content is preferably 4.0% or less. More preferably, it is 3.5% or less, even more preferably, it is 3.2% or less, and most preferably, it is 2.8% or less.

[0067] [Mo: 0.01%~3.50%] Mo is an element that strengthens austenite grain boundaries, and segregates at the grain boundaries to improve the strength of the weld metal. It also has the effect of improving the strength of the weld metal by solid solution strengthening. In order to obtain such an effect, the Mo content is preferably 0.01% or more. More preferably, it is 0.50% or more, even more preferably, it is 1.00% or more, and most preferably, it is 1.50% or more. On the other hand, if it is contained in excess of 3.50%, the effect of increasing the strength of the weld metal becomes limited, and it may precipitate as carbides and become the starting point of fracture, resulting in a decrease in cryogenic impact toughness. Therefore, the Mo content is preferably 3.50% or less. More preferably, it is 3.30% or less, even more preferably, it is 3.10% or less, and most preferably, it is 3.00% or less.

[0068] [B:0.0010% or less] B is one of the elements that segregate at the austenite grain boundaries. If B is mixed in at more than 0.0010%, it forms boron nitride at the austenite grain boundaries, reducing strength, and the boron nitride may become the starting point of fracture, reducing cryogenic impact toughness. Therefore, the B content is preferably 0.0010% or less. More preferably, it is 0.0008% or less, and even more preferably, it is 0.0005% or less.

[0069] [N:0.1200% or less] N is an element that is inevitably mixed in, but if it is contained in excess of 0.1200%, when the welding method of the present invention is used, the amount of N added to the weld metal becomes excessively large, and the intragranular strength becomes excessively strong compared to the intergranular strength, so that fracture occurs from the grain boundary and the cryogenic impact toughness may deteriorate. Therefore, the N content is preferably 0.1200% or less. More preferably, it is 0.1100% or less, and even more preferably, it is 0.1000% or less. On the other hand, N effectively contributes to improving the intragranular strength of the weld metal, stabilizes the austenite phase, and contributes to a stable improvement of the cryogenic impact toughness. To obtain such an effect, the N content is preferably 0.0030% or more. More preferably, it is 0.0040% or more, and even more preferably, it is 0.0060% or more.

[0070] [Optional composition of filler metal] The above-mentioned chemical composition is the basic composition preferred for the filler metal used in the present invention, but in addition to this basic composition, the filler metal may contain the following optional compositions as necessary. They are one or more selected from V: 0.01%-0.04%, Ti: 0.010%-0.040%, Nb: 0.010%-0.040%, Cu: 0.01%-1.00%, Al: 0.010%-0.100%, and W: 0.01%-1.00%. The reasons for limiting these compositions are as follows.

[0071] [V:0.01%~0.04%] V is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating fine carbides. To obtain such an effect, the V content is preferably 0.01% or more. On the other hand, if the V content exceeds 0.04%, the carbides become coarse and become the starting point of cracks during wire drawing of the filler metal, which may reduce the wire drawing workability and the manufacturability of the wire. Therefore, the V content is preferably 0.04% or less.

[0072] [Ti: 0.010%~0.040%] Ti is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating fine carbides. In addition, Ti contributes to suppressing the occurrence of hot cracks by precipitating carbides at the solidification cell interface of the weld metal. In order to obtain such an effect, the Ti content is preferably 0.010% or more. More preferably, it is 0.015% or more, and even more preferably, it is 0.020% or more. On the other hand, if the Ti content exceeds 0.040%, the carbides become coarse and become the starting point of cracks during the wire drawing process of the solid wire, which may reduce the wire drawing processability and the manufacturability of the wire. Therefore, the Ti content is preferably 0.040% or less. More preferably, it is 0.035% or less, and even more preferably, it is 0.030% or less.

[0073] [Nb: 0.010%~0.040%] Nb is a carbide-forming element, and contributes to improving the strength of the weld metal by precipitating carbides. It also contributes to suppressing the occurrence of hot cracks by precipitating carbides at the solidification cell interface of the weld metal. In order to obtain such an effect, the Nb content is preferably 0.010% or more. More preferably, it is 0.015% or more, and even more preferably, it is 0.020% or more. On the other hand, if the Nb content exceeds 0.040%, the carbides become coarse and become the starting point of cracks during the wire drawing process of the solid wire, which may reduce the wire drawing processability and the manufacturability of the wire. Therefore, the Nb content is preferably 0.040% or less. More preferably, it is 0.035% or less, and even more preferably, it is 0.030% or less.

[0074] [Cu:0.01%~1.00%] Cu is an element that stabilizes the austenite phase, and stabilizes the austenite phase even at cryogenic temperatures, thereby improving the cryogenic impact toughness of the weld metal. In order to obtain such an effect, the Cu content is preferably 0.01% or more. More preferably, it is 0.05% or more, and even more preferably, it is 0.10% or more. On the other hand, if the Cu content exceeds 1.00%, the hot ductility decreases, and the manufacturability of the wire may decrease. Therefore, the Cu content is preferably 1.00% or less. More preferably, it is 0.70% or less, and even more preferably, it is 0.50% or less.

[0075] [Al: 0.010%~0.100%] Al acts as a deoxidizer, increases the viscosity of the molten metal, stably maintains the bead shape, and has an important effect of reducing the occurrence of spatter. It also increases the liquidus temperature of the molten metal, contributing to suppression of hot cracking of the weld metal. To obtain such effects, the Al content is preferably 0.010% or more. More preferably, it is 0.020% or more, and even more preferably, it is 0.025% or more. On the other hand, if it is contained in excess of 0.100%, the viscosity of the molten metal becomes too high, and conversely, spatter increases, and the bead does not spread, and defects such as poor fusion increase. Therefore, the Al content is preferably 0.100% or less. More preferably, it is 0.060% or less, and even more preferably, it is 0.050% or less.

[0076] [W:0.01%~1.00%] W is an element that contributes to stabilizing the austenite phase and also contributes to improving strength and cryogenic impact toughness, and can be contained as necessary. In order to obtain such effects, it is preferable that the W content is 0.01% or more. More preferably, it is 0.02% or more, and even more preferably, it is 0.08% or more. If the W content exceeds 1.00%, the amount of coarse carbonitrides increases, which become the starting point of fracture, and the cryogenic impact toughness decreases. For this reason, when W is contained, it is preferable that the W content is 1.00% or less. More preferably, the W content is 0.80% or less, and even more preferably, it is 0.70% or less.

[0077] [Remainder of filler metal composition] The remaining composition other than the above-mentioned chemical composition is composed of Fe and inevitable impurities. Examples of inevitable impurities include H, O, Mg, Zn, Re, etc., and a total of 0.020% or less is acceptable. In addition, as long as the above-mentioned basic composition and optional composition are satisfied, elements other than these may be contained, and such embodiments are also included in the technical scope of the present invention.

[0078] [Chemical composition of weld metal] A welded joint for high Mn steel obtained by the gas tungsten arc welding method of the present invention has improved strength of the weld metal and can further suppress the occurrence of hot cracking.

[0079] The weld metal composition is a mixture (up to about 50%) of the filler metal composition and the base metal composition of high Mn steel.

[0080] A specific composition, in mass%, is preferably C: 0.15% to 0.80%, Si: 0.10% to 1.00%, Mn: 17.0% to 30.0%, P: 0.030% or less, S: 0.030% or less, Al: 0.010% to 0.100%, Cr: 0.4% to 5.5%, Mo: 0.01% to 3.50%, Ni: 0.01% to 10.00%, and N: 0.0400% to 0.4000%. The remainder of the composition is Fe, optional compositions, and unavoidable impurities.

[0081] Among these compositions, the weld metal according to the present invention is characterized in that the N content is preferably 0.0400% to 0.4000%. As described above, N is an element that, when dissolved in a weld metal of a high Mn steel, improves the strength of the weld metal and the welded joint by solid solution strengthening. Furthermore, as the N content increases, there is a tendency for the solid-liquid coexistence temperature range to be narrowed, improving hot cracking susceptibility. In order to obtain such an effect, the N content in the weld metal is preferably 0.0400% or more, and more preferably 0.0500% or more. On the other hand, if the N content exceeds 0.4000%, the amount of dissolved N becomes too large, causing welding defects such as blowholes and pits. Therefore, the N content is preferably 0.4000% or less, and more preferably 0.3500% or less. EXAMPLES

[0082] The present invention will be further described below with reference to examples. However, the following examples are merely intended to illustrate and explain the present invention in more detail, and are not intended to limit the scope of the present invention.

[0083] Molten steel was produced in a vacuum melting furnace, cast into a mold, and then bloomed into slabs (thickness: 150 mm) having the composition shown in Table 1 to obtain steel materials. The obtained steel materials were then charged into a heating furnace, heated to 1250°C, and hot-rolled to a finish rolling temperature of 850°C, and immediately water-cooled to obtain steel materials (high Mn steel) with plate thicknesses of 12 mm and 30 mm.

[0084] [Table 1]

[0085] Next, molten steel having the composition shown in Table 2 was melted in a vacuum melting furnace and cast into a 1000 kg steel ingot. The obtained steel ingot was heated to 1200°C, hot rolled, then cold rolled, and annealed (900°C to 1200°C) as necessary to obtain a TIG welding filler material (filler rod) having a diameter of 2.0 mm and a length of 1000 mm.

[0086] [Table 2]

[0087] Next, the obtained steel material (plate thickness 12 mm) was butted together in accordance with JIS Z 3121 to form a 45° V groove, and TIG welding was performed using the obtained TIG welding filler material (filler rod) as a welding material in the combination shown in Table 3 to form a weld metal in the above-mentioned groove to obtain a welded joint. The TIG welding was performed using each filler material (diameter 2.0 mmφ) with the composition shown in Table 2, without preheating, in a downward position, under conditions of current: 200 A to 230 A (DCEN), voltage: 12 V to 16 V, welding speed: 8 cm / min to 14 cm / min, and interpass temperature: 100 ° C to 150 ° C (welding conditions are shown in Table 3). The electrode was a pure tungsten rod (3.2 mmφ).

[0088] [Weld metal composition analysis] In the weld metal part of the welded joint, a 5 mm square block was taken from the center of the plate thickness and the center of the weld line, and the total N content in the weld metal was measured by the inert gas fusion-thermal conductivity method.

[0089] [Evaluation of hot crack resistance] After welding, a 10 mm thick macro test piece was taken from the center position in the weld line direction with a microcutter, with the observation surface being a cross section perpendicular to the weld line, and the cross section of the weld metal was observed with an optical microscope (30x) to determine the presence or absence of hot cracking. Here, in the test pieces where hot cracking was observed, a long and narrow black area measuring 25 μm wide and 80 μm long or more was observed. If hot cracking was observed, it was judged as "present," and if no cracking was observed, it was judged as "absent." The presence or absence of pits or blowholes was also judged.

[0090] Furthermore, flat test pieces measuring 5 (t) mm × 50 (w) mm × 100 (l) mm were cut out from the welded joint. At this time, the surface ground 1 mm from the joint surface was used as the test piece surface, and the remaining thickness was ground from the back side so that the test piece thickness was 5 mm. Then, the hot cracking susceptibility of the weld metal part of the joint was evaluated by a trans-Varestraint test. In this test, melt-run welding was performed using a TIG arc, and the yokes on both ends of the test piece were suddenly dropped at the same time as the arc was extinguished, thereby applying tensile strain and forcibly generating hot cracks on the bead surface. The applied strain was 2.4% to 5.8%, which corresponds to the saturation strain value of the maximum crack length. The solidification brittleness temperature range [BTR (K)] was calculated from the saturation value of the maximum cracking strain obtained at each strain, and the hot cracking susceptibility of each material was evaluated.

[0091] [Evaluation of weld metal properties] Tensile test pieces (parallel portion diameter 6 mmφ) were taken from the obtained welded joints and subjected to tensile tests in accordance with the provisions of JIS Z 3111. The tensile tests were performed on three pieces each at room temperature, and the average values ​​obtained (0.2% proof stress, tensile strength) were regarded as the tensile properties of the welded metal of the welded joints.

[0092] Charpy impact tests were also conducted on the weld metal in accordance with the provisions of JIS Z 3128. The positions at which the test pieces (V notch) were taken are shown in Figure 2. The direction of the V notch 8 of the test piece 6 was perpendicular to the surface of the base metal 1, and the position of the V notch 8 was set to the midpoint of the fusion line 5 of the weld metal 2 on the center line 7 of the test piece, and the test piece 6 was taken from a position 1 mm below the surface of the base metal 1. Charpy impact tests were also conducted on three pieces of each in the same manner, and the absorbed energy ( v E -196 ) was calculated, and the average value was regarded as the cryogenic impact toughness of the weld metal of the welded joint.

[0093] As mentioned above, the target value of the present invention is that the room temperature yield stress (0.2% proof stress) and tensile strength of the weld metal are improved by an average of 10 MPa or more compared to conventional TIG welded joints in which the shielding gas is 99.5% or more Ar gas or He gas, with the remainder consisting of unavoidable impurities. Furthermore, the Charpy impact test absorption energy ( v E -196 ) is 28J or more.

[0094] The results obtained are shown in Table 3.

[0095] [Table 3]

[0096] None of the welded joints produced in the examples of the present invention were welded joints that did not suffer from hot cracking during welding and had excellent hot cracking resistance. Compared to conventional TIG welded joints in which the shielding gas is 99.5% or more Ar gas or He gas, with the remainder consisting of unavoidable impurities, the yield stress (0.2% proof stress) and tensile strength were improved by an average of 10 MPa or more, and the BTR was reduced, improving the hot cracking susceptibility. Furthermore, the weld metal had a yield stress (0.2% proof stress) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 ) of 28 J or more, resulting in excellent mechanical properties.

[0097] In addition, joint No. 18 is an example (comparative example) of a welded joint using a steel material with a Mn content of 16.2 mass% instead of the high Mn steel of the present invention, and although it has low Charpy impact absorption energy and low toughness, by mixing nitrogen gas into the shielding gas, the strength was improved and no hot cracking occurred. From this result, it was found that there is an effect of improving the strength of the welded joint by simply mixing nitrogen gas into the shielding gas, even without adjusting the composition of the base metal or welding material.

[0098] In joints No. 4, 8, 19, 22, and 25, the N2 gas content in the shielding gas was excessive, and there were many pits and blowholes, making them unsuitable as welded joints. As a result, it was not possible to take tensile test pieces or Charpy impact test pieces, and it was not possible to determine whether or not there was hot cracking, so in Table 3 they are listed as "not identifiable."

[0099] [Relationship between N2 content in shielding gas and strength of weld metal] Based on the data in Table 3, the changes in 0.2% proof stress and tensile strength versus the N content in the weld metal were organized for each nitrogen content in the shielding gas. Figure 3 shows the changes in 0.2% proof stress versus the N content in the weld metal, and Figure 4 shows the changes in tensile strength versus the N content in the weld metal. Here, the results were grouped and organized according to the nitrogen content of the shielding gas.

[0100] As can be seen from Fig. 3, when the nitrogen gas content in the shielding gas is changed for the same steel material and the same filler metal combination, the 0.2% proof stress is higher when the nitrogen gas content is 2% by volume than when there is no nitrogen gas, and is even higher when the nitrogen gas content is 5% by volume. In the case of the tensile strength in Fig. 4, the tensile strength increases as the nitrogen content increases from 2% by volume to 5% by volume. Therefore, according to the data in Table 3, it can be seen that the strength of the weld metal increases by 10 MPa or more as the nitrogen gas content increases in all combinations. From these facts, it was confirmed that the use of the shielding gas containing nitrogen gas according to the present invention is effective in improving the strength of the weld metal. [Explanation of symbols]

[0101] 1 Base material (steel material) 2. Weld metal 2a Weld metal layer 3 Bevel surface 4 Solidification cracking 5. Melting Line 6 Test specimens 7. Center line of test piece 8 V-notch t Plate thickness θ Bevel angle

Claims

1. In a gas tungsten arc welding method in which steel materials are welded using a shielding gas and a filler metal, The metal structure of the steel material has an austenite phase, The Mn content of the steel material is 18.0% to 30.0% by mass, The shielding gas contains 0.5% to 10.0% nitrogen gas by volume, with the remainder being an inert gas and unavoidable impurities.

4. A gas tungsten arc welding method comprising the steps of:

2. The steel material further comprises, in mass%, C: 0.10% to 0.70%, Si: 0.05% to 1.00%, P: 0.030% or less, S: 0.007% or less, Al: 0.010% to 0.070%, Cr: 2.5% to 7.0%, N: 0.0050% to 0.0500%, O (oxygen): 0.0050% or less The balance is Fe and unavoidable impurities.

2. The gas tungsten arc welding method according to claim 1 .

3. The steel material further comprises, in mass%, Mo: 0.01% to 2.00%, V: 0.01% to 2.00%, W: 0.01% to 2.00%, Ni: 0.01% to 4.00%, REM: 0.0010% to 0.0200%; B: 0.0005% to 0.0020% Contains one or more selected from the following:

3. The gas tungsten arc welding method according to claim 2.

4. The filler metal comprises, in mass %, C: 0.20% to 0.80%, Si: 0.15% to 1.00%, Mn: 17.0% to 30.0%, P: 0.030% or less, S: 0.030% or less, Ni: 0.01% to 10.00%, Cr: 0.4% to 4.0%, Mo: 0.01% to 3.50%, B: 0.0010% or less, N: 0.1200% or less The balance is Fe and unavoidable impurities.

4. A gas tungsten arc welding method according to claim 1, wherein the arc welding is performed in a gas tungsten arc.

5. The filler metal further comprises, in mass %, V: 0.01% to 0.04%, Ti: 0.010% to 0.040%, Nb: 0.010% to 0.040%, Cu: 0.01% to 1.00%, Al: 0.010% to 0.100% and W: 0.01% to 1.00% Contains one or more selected from the following:

5. The gas tungsten arc welding method according to claim 4.

6. In the gas tungsten arc welding method, Welding current is 180A to 250A, Welding voltage is 10V to 20V, Welding speed: 5cm / min to 30cm / min The welding heat input is 7.0 kJ / cm to 40.0 kJ / cm 4. A gas tungsten arc welding method according to claim 1, wherein the arc welding is performed in a gas tungsten arc.

7. In the gas tungsten arc welding method, Welding current is 180A to 250A, Welding voltage is 10V to 20V, Welding speed: 5cm / min to 30cm / min The welding heat input is 7.0 kJ / cm to 40.0 kJ / cm 5. The gas tungsten arc welding method according to claim 4.

8. In the gas tungsten arc welding method, Welding current is 180A to 250A, Welding voltage is 10V to 20V, Welding speed: 5cm / min to 30cm / min The welding heat input is 7.0 kJ / cm to 40.0 kJ / cm 6. The gas tungsten arc welding method according to claim 5.

9. The weld metal has a yield stress (0.2% yield strength) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 ) is 28J or more 4. A gas tungsten arc welding method according to claim 1, wherein the arc welding is performed in a gas tungsten arc.

10. The weld metal has a yield stress (0.2% yield strength) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 ) is 28J or more 5. The gas tungsten arc welding method according to claim 4.

11. The weld metal has a yield stress (0.2% yield strength) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 ) is 28J or more 6. The gas tungsten arc welding method according to claim 5.

12. The weld metal has a yield stress (0.2% yield strength) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 ) is 28J or more 7. The gas tungsten arc welding method according to claim 6.

13. The weld metal has a yield stress (0.2% yield strength) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 ) is 28J or more 8. The gas tungsten arc welding method according to claim 7.

14. The weld metal has a yield stress (0.2% yield strength) of 400 MPa or more, a tensile strength of 600 MPa or more, and a Charpy impact absorption energy ( v E -196 ) is 28J or more 9. The gas tungsten arc welding method according to claim 8.

Citation Information

Patent Citations

  • Welding method of double pipe

    JP1984218281A

  • Weld joint, weld material therefor, and welding method

    JP2017035724A

  • Weld joint and production method therefor

    JP2022053860A

  • Gas Metal Arc Welding Method

    JP7494966B1

  • Method for producing high-strength welded joint for cryogenic environments

    WO2020203335A1